2014
DOI: 10.1371/journal.pcbi.1003933
|View full text |Cite
|
Sign up to set email alerts
|

Low Probability of Initiating nirS Transcription Explains Observed Gas Kinetics and Growth of Bacteria Switching from Aerobic Respiration to Denitrification

Abstract: In response to impending anoxic conditions, denitrifying bacteria sustain respiratory metabolism by producing enzymes for reducing nitrogen oxyanions/-oxides (NOx) to N2 (denitrification). Since denitrifying bacteria are non-fermentative, the initial production of denitrification proteome depends on energy from aerobic respiration. Thus, if a cell fails to synthesise a minimum of denitrification proteome before O2 is completely exhausted, it will be unable to produce it later due to energy-limitation. Such ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…This evolutionary strategy, called bet hedging, enables a population to prepare for a potential switch to a new environmental condition by harboring a subpopulation that is pre-adapted to the new environment. Bet hedging has been characterized in a number of microbial systems and shown to play a role in many processes, including pathogenesis (Ackermann et al, 2008; Stewart and Cookson, 2012), antibiotic persistence (Balaban et al, 2004; Maisonneuve and Gerdes, 2014; Verstraeten et al, 2015; Wakamoto et al, 2013), cellular differentiation (Veening et al, 2008b), regulation of metabolism (Hassan et al, 2014; Kotte et al, 2014; Ratcliff and Denison, 2010), induction of stress responses (Sureka et al, 2008), and viral latency (Maslov and Sneppen, 2015; Rouzine et al, 2015). Stochasticity in gene expression is often responsible for the generation of phenotypic diversity in these systems and frequently results in a bimodal distribution of phenotypes (Kotte et al, 2014; Nielsen et al, 2010; Ozbudak et al, 2004; Veening et al, 2008b), although bimodality is not always observed (El Meouche et al, 2016; Levy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This evolutionary strategy, called bet hedging, enables a population to prepare for a potential switch to a new environmental condition by harboring a subpopulation that is pre-adapted to the new environment. Bet hedging has been characterized in a number of microbial systems and shown to play a role in many processes, including pathogenesis (Ackermann et al, 2008; Stewart and Cookson, 2012), antibiotic persistence (Balaban et al, 2004; Maisonneuve and Gerdes, 2014; Verstraeten et al, 2015; Wakamoto et al, 2013), cellular differentiation (Veening et al, 2008b), regulation of metabolism (Hassan et al, 2014; Kotte et al, 2014; Ratcliff and Denison, 2010), induction of stress responses (Sureka et al, 2008), and viral latency (Maslov and Sneppen, 2015; Rouzine et al, 2015). Stochasticity in gene expression is often responsible for the generation of phenotypic diversity in these systems and frequently results in a bimodal distribution of phenotypes (Kotte et al, 2014; Nielsen et al, 2010; Ozbudak et al, 2004; Veening et al, 2008b), although bimodality is not always observed (El Meouche et al, 2016; Levy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In other denitrifiers, similar gas kinetics have been taken to suggest that only a small fraction of cells synthesize the core denitrification enzymes and then grow exponentially. This phenomenon has been explored by modelling and experiments in the α‐proteobacterium P. denitrificans , where a low probability of nirS expression and high probability of nar expression results in nitrite accumulation, followed by its reduction by a minority of NIR positive cells (Hassan et al, ; ; Lycus et al, ). In H. denitrificans , there is no significant accumulation of nitrite, thus, the gatekeeper appears to be NAR.…”
Section: Discussionmentioning
confidence: 99%
“…S5, S7, S8 and S10). By plotting VenormalO2, Venox and Vetot ( VenormalO2 + Venox) against time, we were able to inspect if the transition from aerobic to anaerobic respiration resulted in a long lasting depression of respiratory metabolism, as observed in similar experiments with Paracoccus denitrificans (Bergaust et al , ; Hassan et al , ).…”
Section: Methodsmentioning
confidence: 99%